Emotional intelligence and psychological capital: What is the role of workplace spirituality? - Mónico,Lisete (2016)
BACKGROUND: Workplace Spirituality is understood as the sense of community in the group, alignment with organizational values, sense of usefulness to the community, hapiness in work, and the oportunities for inner life. Organizations that encourage Workplace Spirituality achieve higher revenues and increase employee commitment, reducing absenteeism and depression. We believe that Workplace Spirituality can play a significant role in the relationshipbetween Emotional intelligence and Psychological Capital. AIM:To analyze the moderator or mediator role of Workplace Spirituality in the relationshipbetween Emotional Intelligence and Psychological Capital. METHODS: A quantitative survey was made with a sample of 301 workers who answered the Emotional Intelligence Scale, PsyCapQuestionnaire, and Workplace Spirituality Questionnaire. Reliability and validity analysis ensured a trusted use of these measures. RESULTS: We found a significant relationshipbetween Emotional Intelligence and Workplace Spirituality (r=.358) and between Emotional Intelligence with Psychological Capital (r=.599). Together, the five dimensions of Workplace Spirituality had a predictive capacity of 33% of the Psychological Capital. The relationshipbetween Emotional Intelligence and Psychological Capital was slightly moderated by Workplace Spirituality (p=.024). Furthermore, Workplace Spirituality was a partial mediator on the relationshipbetween Emotional Intelligence and Psychological Capital (direct effect of β<=.55, indirect effect of β=.17, p<.05). CONCLUSION: Workplace Spirituality, Emotional Intelligence, and Psychological Capital are positively correlated. Workplace Spirituality affects the relationshipbetween Emotional Intelligence and Psychological Capital, acting as a moderator variable (small effect size). Workplace Spirituality is a partial mediator on the relationship between Emotional Intelligence and Psychological Capital.